Global perspectives on E-commerce taxation law - Basu, Subhajit (Markets and the law, 2007)
In its most advanced form, e-commerce allows unidentified purchasers to pay obscure vendors in "electronic cash" for products that are often goods, services and licenses all rolled into one. This book considers the implications for the domestic and international tax systems of the growth of e-commerce, covering a wide variety of activities, from discussion of the principles governing direct and indirect taxation, to explanation of the implementation and use of e-commerce on the part of businesses, as well as the application of existing tax principles in this field. With its focus on the broader issues surrounding the expansion of e-commerce and its attention to the problems arising internationally in this field, "Global Perspectives in E-Commerce Taxation Law" will appeal to scholars worldwide.